CURRENT ISSUES OF THE ORGANIZATION OF ECONOMIC PROCESSES OF TRADE ENTERPRISES IN UKRAINE: ANALYSIS OF ECONOMIC LEVERS OF DEVELOPMENT, TEAM FORMATION, EFFECTIVE SELECTION AND PROMOTION - SEMENCHA, Ilona; YAROVENKO, Tetiana; KURYACHA, Natalia; HORDIEIEVA-HERASYMOVA, Liudmyla (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines topical issues of organizing economic processes of trade enterprises in Ukraine. Attention is paid to the importance of economic analysis, which helps to determine the efficiency of an individual trade enterprise. Ethical codes of the enterprise have been established, which directly relate to four main areas. The activities of enterprises that buy goods and sell them without further processing are considered in more detail. For trade enterprises, it is extremely important to have productive and coordinated work teams, to pay due attention to recruiting as one of the areas of business management, and to use social networks in business. All this has a great impact on the successful development of trade enterprises in today's changing market. Trading businesses have to struggle in today's highly competitive environment to be the best and thus gain customer loyalty. From the point of view of a potential client of a trade enterprise, competitiveness is the ability of a business to be efficient and realize its sales volumes on the market of goods and services, from the point of view of owners, competitiveness can be considered as the ability of a company to effectively attract financial resources. Therefore, it is possible to assess competitiveness using different methods.Trade can be defined as a way of ensuring the circulation of goods. It ensures the transition of goods and services from the sphere of material production to the sphere of trade and services. The basis of this activity is the acquisition of goods, services and other valuables for the purpose of resale, rental or transfer for use for a certain fee.It is extremely important for trade enterprises to have productive and cohesive work teams. The composition and nature of the work group depends on the individual employees who make up this group.  A condition for creating an effective group is the integration of motivated and creative employees of trade enterprises into it. Team building should not just be a random process of grouping people together, but a purposeful effort by managers to create a productive work team.The success of a business is determined by the working potential it has. It means not only the number of employees, but also their talents, abilities and skills, sufficient to achieve the set goals and fulfill the company's mission. Thus, hiring such employees is one of the most important and permanent activities of personnel management.
Keywords: economic analysis; business processes; trade; business organization; team building; recruiting; social networks; time management